Creative tourism microentrepreneurs in Portugal - Bakas, Fiona Eva (2020)
When researching the role of microentrepreneurship in equitable and sustainable development, the question of how tourism microentrepreneurs forge relationships between place, community, and resources is significant. Two case studies from CREATOUR, a project investigating creative tourism, a novel type of cultural tourism that includes active participation in creative activities and connection to place, bring to light how these relationships are developed and implemented. Findings indicate that creative tourism microentrepreneurs’ activities in two small cities are being shaped by, and shaping, place in multifaceted ways. Creative tourism activities stimulate new perspectives on place, are designed synergistically with the ‘seasonal’ fluctuations of the type of visitors, are embedded in personal networks of collaborators, and actively encourage alternative patterns of tourism consumption.